Length-weight relationship and condition factor of bullet tuna (Auxis rochei Risso, 1810) in the waters of Mamuju District, West Sulawesi Province, Indonesia - MUHAMMAD NUR; TENRIWARE TENRIWARE; ADIARA FIRDHITA ALAM NASYRAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nur M, Tenriware, Nasyrah AFA. 2023. Length-weight relationship and condition factor of bullet tuna (Auxis rochei Risso, 1810) in the waters of Mamuju District, West Sulawesi Province, Indonesia. Biodiversitas 24: 5253-5259. Bullet tuna (Auxis rochei Risso, 1810) is a fish species with a wide distribution and high socioeconomic value. Furthermore, it serves as a primary catch for fishermen, offering a crucial protein source to the community and generating employment opportunities in various sectors, including fresh fish sales, fish freezing, drying, and smoking industries. To maintain the sustainability of bullet tuna, it is necessary to know basic information regarding the study of length-weight relationship and condition factors because it is related to the fish growth and condition of fish in their habitats. Therefore, this study aimed to determine the growth pattern of bullet tuna, fundamental data for sustainable management efforts. The investigation was conducted from May to August 2023, and the sample fish were collected at the Fish Landing Port (PPI) Kasiwa, Mamuju District, West Sulawesi Province. Analysis was conducted in the Fisheries Department Laboratory, Sulawesi Barat University. The study procedures involved determining the total length and weight of the fish using a measuring instrument and digital scale, respectively, with accuracies of 0.1 mm and 0.01 g. Based on the data collected, 302 samples were obtained, consisting of 187 males and 115 females. The results showed that the relationship between the length and weight of bullet tuna yielded the equations of W = 0.027L3.4783 for male fish, W = 0.0052L3.2732 for female fish, and W = 0.0033L3.4141 when combined. A t-test was conducted on the coefficient b, showing a calculated t-value greater than the tabulated values. It indicated that bullet tuna belongs to the negative allometric growth type (minor) (b<3), where body weight increased faster than body length. Condition factors for male and female fish ranged from 0.3186 to 1.6961 and 0.6990 to 1.5011, respectively, with averages of 0.9957 and 0.7997. It indicates that the bullet tuna fish are in good condition in Mamuju District water.